Effects of graphene oxide and collagen type I on modulating proliferation and gene expression of mesenchymal stem cells - Haselamirrah Mohd Akhir (2021)
Mesenchymal stem cells derived from amnion (AM-MSCs) has the ability of self-renewal and multilineage differentiation capacity to generate adipocytes and osteoblasts. However, there are limitations for continuous stem cells culture in term of cell supply and the differentiation capacity of amnion-derived MSCs. Progresses in biomaterials engineering enable the study of MSCs in in vitro cell expansion system to overcome this limitation. Biomaterials create a physical environment which can manipulate cells without any requirement for chemical factors. This study aimed to investigate how graphene oxide (GO) and collagen (COL) modulate proliferation, stemness and differentiation potentials of AM-MSCs. AM-MSCs were isolated and cultured in DMEM/F12 media. AM-MSCs were grown in osteogenic and adipogenic condition with and without the presence of biomaterials. RT-PCR determined the expression of genes involved in self-renewal and differentiation genes. The roles of MAPK pathways in regulatin AM-MSCs were done using Western Blot. The results showed that AM-MSCs exhibited spindle-shaped like cells morphology. AM-MSCs cultured in both GO and COL plates showed comparable proliferation as compared to the controls. However, both biomaterials altered the stemness markers and differentiation genes differently. Results showed elevated expressions of stemness (OCT3/4 & NANOG), osteogenic (RUNX2 & OCN) and adipogenic (CEBPA & CEBPB) genes when cells cultured in the presence of COL for both basal and osteo-adipogenic condition. In the presence of GO without induction, the expression of stemness and osteogenic genes were maintained but not adipogenic genes. In AM-MSCs-GO sample, stemness genes were either suppressed or unaltered. Surprisingly, suppression of adipogenic genes (CEBPA & CEBPB) was observed in AM-MSCs-GO whereby osteogenic genes showed little effect. Besides that, the presence of collagen had some effect in upregulating the expression of the histone acetyltransferase (hMOF) and DNA methyltransferase (DNMT3A & DNMT3B), but little changes were found in GO samples. In addition, activation of ERK and p38 pathways were affected by COL but not GO. In conclusion, these results demonstrated that collagen enhanced both osteo-adipogenic differentiation in AM-MSCs, while graphene oxide has a much more reserved lineage-specific differentiation.